The Influence of The Accounting Method Selection for Merger and Acquisition on the Stock Price of Public Companies in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
When one company acquires another company, based on the economic substance of the acquisition, the transaction should be recorded following either the purchase method or the pooling of interests method. The use of pooling accounting will normally produce higher reported after tax income than that of the use of purchase accounting. Purchase accounting requires that the investment be recorded at the fair market value of the acquired assets. The objective of this study is to investigate whether there is a significant difference on the stock price of public companies involved in merger and acquisition, as between the period before and after the first publication of consolidatedfinancial statements. More important, is that the study also investigates the accounting method used, and the type of acquisition selected in merger and acquisition, and how market reacts to accounting method selection. The study analyzes 57 cases of merger and acquisition in the period of January 1990 to June 1997. The result of the analysis shows that there is a significant decrease in the average stock price as between the periods before and after the date of consolidated financial statement publication. The result of the study provides empirical evidence that the activities of merger and acquisitions affects significantly the investment decision made by the investor as reflected in the stock price.